ANALYSIS STRUCTURE THE PT. TEMPO LAND BUILDING - Subhan Manthofani; Arief Firmanto (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2017)
Mundu is an area in the district of Cirebon that passed by the Pantura lane, in the area of the Mundu there are various kinds of trading industry, one of which is the trading industry from PT. TEMPO LAND that are producing medicines for health. In order to create a good production and marketing, so in the area is built office production and marketing of PT. TEMPO LAND.PT. TEMPO LAND is a group company in the form of by the TEMPO GROUP or PT. TEMPO SCAN PACIFIC Tbk . The company PT. TEMPO GROUP started its business on November 3, 1953. Production from this company produces a variety of pharmaceutical and healthcare products with different brands. In order to create a structure that is safe and meets serviceability limit, so in the process of design the building structure must be according to SNI - 2847 - 2013 of reinforced concrete, which is the latest regulations adapted from the latest material technology development refers to the AISC. Beside planning, the loading structure must be according to SNI – 1727 – 2013 , then for calculation of earthquake engineering refers to SNI – 1726 – 2012.Analysis structure using SAP2000, for the material of structures is used concrete including frame section (column, sloof, beam, and slab). And then the result from analysis are the PT. TEMPO LAND building is safe or not, with check the deflection and check load maximum permit from analysis foundation of PT. TEMPO LAND.Keywords : Analysis structure, SAP2000, frame section, deflection.